Seaweed extracts with antifungal and biostimulatory effects: the next generation formulation towards sustainable crop production - Johari, Nur Asna Faiqah; Syd Ali, Nusaibah; Abdul Wahab, Mohd As’wad; Asib, Norhayu; Balia Yusof, Zetty Norhana (2023)
Fungal phytopathogens are a growing problem all over the world as they cause significant crop losses, affecting the quality of fruits and vegetables, and diminishing the availability of food. For oil palm, a fungal pathogen Ganoderma boninense, affects the quality of palm oil produced leading to huge loss every year. The use of synthetic chemicals has been known to be the most common method of disease management but unfortunately hazardous to the environment. A more environmentally friendly and sustainable remedy is of great interest. Seaweeds, one of the richest marine sources of compounds possessing a wide range of bioactivities, present an eco-friendly alternative in the search for diverse compounds with industrial applications. Seaweed extracts have been shown to possess antifungal components and growth-stimulating activities and used as biostimulants in crop production. This project described the antifungal and biostimulatory potential of selected locally sourced seaweed extracts in oil palm. On top of that, the initiation of formulation of seaweed-based antifungal/biostimulant products, and the cultivation potential of the selected seaweeds are currently being explored. This project is hoped to utilize local seaweeds as a source of greener and safer products for the stress and disease mitigation strategies not only for the oil palm industry, but also for other food crops and vegetables, in line with the sustainable development goals of zero hunger and responsible consumption and production.